2018
DOI: 10.1891/1058-1243.27.4.198
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers to Exercise in the First Trimester of Pregnancy

Abstract: Regular physical activity has been shown to improve pregnancy outcomes. We sought to identify barriers to exercise during the first trimester of pregnancy. Five hundred forty-nine pregnant women in their first trimester rated barriers to exercise on a scale of 1 (not a barrier) to 5 (a huge barrier) and recorded physical activity (minutes/week). Women were placed into one of three classifications, nonexercisers (zero exercise), infrequent exercisers (<150 minutes/week), or exercisers (≥150 minutes/week). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 42 publications
6
24
1
1
Order By: Relevance
“…which are not frequently included in questionnaires and that are therefore difficult to quantify with self-reported strategies. The proportion of women reporting PA levels that meet international guidelines in our study are remarkably greater than has been reported in much of the literature [29][30][31]35,37,38], with the exception of the study by Sytsma and colleagues [39]. However, it should be acknowledged that studies reporting relatively lower PA typically remove periods of time below 10 minutes from their PA calculation.…”
Section: Pa Levels During Pregnancy and Agreement Between Self-reportcontrasting
confidence: 60%
See 2 more Smart Citations
“…which are not frequently included in questionnaires and that are therefore difficult to quantify with self-reported strategies. The proportion of women reporting PA levels that meet international guidelines in our study are remarkably greater than has been reported in much of the literature [29][30][31]35,37,38], with the exception of the study by Sytsma and colleagues [39]. However, it should be acknowledged that studies reporting relatively lower PA typically remove periods of time below 10 minutes from their PA calculation.…”
Section: Pa Levels During Pregnancy and Agreement Between Self-reportcontrasting
confidence: 60%
“…While many studies have also found that women with at least one previous child are more inactive during pregnancy [7,32,[40][41][42]44,45], Watson et al [46] found the opposite pattern of results; still others have found no statistically significant association between parity and PA during pregnancy [31,47]. The relationship between race and exercise is not consistent, with some studies finding that exercisers are more likely to be white [35,39,41], while others found similar exercise rates among black and white women [43,44]. Some others indicated that there is no relation between ethnic origin and PA [31,32,48].…”
Section: Physical Activity During Pregnancy: On Guidelines Performanmentioning
confidence: 99%
See 1 more Smart Citation
“…Various factors have been shown to influence PA participation among pregnant women, including low maternal education [ 55 57 ], unemployment [ 58 , 59 ], pregnancy symptoms/discomforts [ 3 , 55 , 60 – 62 ], multiparity [ 63 ], lack of strength or fatigue [ 3 ], lack of time [ 3 , 55 , 60 ], lack of motivation [ 56 , 64 , 65 ], and safety concerns or fear [ 62 , 66 ]. Some studies have reported cultural and religious beliefs [ 66 ], lack of social support [ 61 , 67 ] and other responsibilities [ 61 , 68 ].…”
Section: Introductionmentioning
confidence: 99%
“…Worryingly, less than 50% of women adhere to the prenatal PA guidelines set by various bodies to promote a healthy pregnancy [58]. The intrapersonal factors limiting the participation of pregnant women in PA include low levels of maternal awareness and education on the benefits of PA during pregnancy [2,57], pregnancy symptoms and discomfort [2,57,59,60], multiparity [61], lack of strength or fatigue [57,59,62,63], lack of time [57,59,62,64], lack of motivation [57,62,63,65], lack of self-confidence [57,66] and lack of safety or fear [57,67,68]. Interpersonal or social factors affecting PA during pregnancy are cultural and religious beliefs [69,70], lack of social support [71,72], having child care responsibilities [59,71,73] and work and family responsibilities [49,59,62,63].…”
Section: Introductionmentioning
confidence: 99%